A formação de professores e uma extensionista: cartografando uma experiência - Hartmann, Marília Regina (2012)
This dissertation is inserted in the Postgraduate Program in Education, Federal University of Santa Maria, integrating Research Line 1: Education, Knowledge and Professional Development. This research sought to follow the process of an extension project, performed by the Group of Studies and Research in Social Education and Imaginary (GEPEIS) and their subsequent movements, throughout the year 2011, in Santa Maria town, RS. Accordingly, the objective of this study was to construct cartography, from the experiences about the project University-Society: a collective action by formation women, to identify possible relationships with teacher formation. Depending on this, were also established the following specific objectives: to map the extension action experienced in the relevant project and the later movements and identify relationships between the extension project developed and teacher formation. This project is justified by the need to expand the research in relation to the extension actions developed by higher education institutions, as well as looking at the possibilities of formation of participants in these areas. The theoretical framework includes the following themes: Education, Extension, Device and Cartography. As methodological tool, was used the cartography, which directs to follow the process and, working from the perspective of constructing data throughout the research. From this work, it was possible to identify different devices that can help in the teachers formation, from space that is made possible by extension, thus, pointing to the need to evaluate the extensions as a formation place.